Sosialisasi Menumbuhkan Semangat Siswa Sekolah Dasar Dalam Mewujudkan Impian Bagi Masa Depan Yang Cemerlang di SD Plus Al-Muhajirin Purwakarta - Hisny Fajrussalam; Alsina Raisa Dzakira Robbaniah; Annisa Windar Khasanah; Asri Apri Tri Lianti Putri; Buldansyah Buldansyah; Elviana Ramdayanti (Jurnal Pelayanan Hubungan Masyarakat, 2023)
Dreams can be considered as dated hopes. Therefore, everyone should possess them in order to have life goals and work towards turning those dreams into reality. Dreams are like trees that continually grow – the more they are nurtured, cared for, and protected, the stronger their roots become, the lusher their leaves, and the more abundant their fruits. This also applies to children. Often, adults perceive children's dreams as mere fantasies, yet there are also many adults who have successfully realized their childhood dreams. This signifies that the dreams they have can develop and bring about impacts that children can experience in their interests during the learning process (Styawan et al., n.d.). Almost the majority of participants do not yet grasp the significance of their dreams and the benefits they will feel in the future. This study aims to provide an understanding to students regarding the concept of dreams and the benefits that will experience improvement. This can be proven by the students' self-confidence in writing down the dreams they want to achieve through the dream tree that has been provided. Therefore, university students conducting the socialization of dreams and aspirations to elementary school students can provide them with the motivation and inspiration to strive towards their dreams, aspirations, and hopes for the future. The hope is that this socialization activity can have a positive impact on students by equipping them with self-confidence in the dreams they aspire to.